Introducing barley as aphid reservoir in sweet-pepper greenhouses: Effects on native and released hoverflies (Diptera: Syrphidae) - Pineda, A.,University of Alicante (Spain). Biodiversity Research Inst; Marcos-Garcia, M.A.,University of Alicante (Spain). Biodiversity Research Inst (European journal of entomology, 2008)
Habitat management is a form of conservation biological control that includes strategies such as the provision of alternative prey for natural enemies. One example is the banker plants strategy which consists of introducing cereals with aphids in horticultural crops. It is usually combined with parasitoid releases. In this work we evaluated whether aphid-infested barley as banker plants enhances native populations of aphidophagous syrphids and extends the residence time of Episyrphus balteatus following release. The work was performed in four replicated sweet-pepper commercial greenhouses in the southeast of Spain. Barley was sown, and infested with the aphid Rhopalosiphum maidis. Visual censuses were performed to record released individuals of E. balteatus (marked on the thorax before release) and naturally occurring hoverflies. At the end of the experiment leaf samples were taken to the laboratory, and the immature syrphids were reared for identification. The occurrence of syrphids that come from outside the greenhouse was significantly increased by the presence of the infested barley plants. From a total of 506 observations of adult native syrphids, 81% were Sphaerophoria rueppellii. We did not find significant differences between control plots and those provided with banker plants in their probabilities to retain released specimens of E. balteatus. Of the syrphids collected at immature stages from the barley leaves, we did not record any E. balteatus, and 100% of the specimens were identified as S. rueppellii. We conclude that the banker plant strategy is effective in attracting natural populations of syrphids into sweet pepper greenhouses, but not in keeping released individuals of E. balteatus in the greenhouses long enough to lay eggs. We suggest that the E. balteatus release method should be amended.